2017
DOI: 10.18549/pharmpract.2017.01.894
|View full text |Cite
|
Sign up to set email alerts
|

Consumer views on safety of over-the-counter drugs, preferred retailers and information sources in Sweden: after re-regulation of the pharmacy market

Abstract: Background:The availability of over-the-counter drugs (OTCs) has increased in Sweden since a re-regulation of the pharmacy market in 2009, through which non-pharmacy retailers became permitted to provide certain OTCs.Objective:To examine the adult general public’s views on safety, purchasing and information channels, storage and disposal of OTCs in Sweden, three years after the re-regulation of the pharmacy market.Methods:A questionnaire study in 2012-13 in a stratified, random sample of all inhabitants in Swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 19 publications
0
18
0
3
Order By: Relevance
“…Its main purpose is to provide patients with the necessary information about their medication in terms of its administration, precautions, and potential side effects. 34 In our study, gender was highly associated with reading OTC product leaflets including side effects, contraindications, and proper storage conditions (P < .05). These findings were in line with what was found in Palestine where gender was the only associated factor with reading the PIL.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Its main purpose is to provide patients with the necessary information about their medication in terms of its administration, precautions, and potential side effects. 34 In our study, gender was highly associated with reading OTC product leaflets including side effects, contraindications, and proper storage conditions (P < .05). These findings were in line with what was found in Palestine where gender was the only associated factor with reading the PIL.…”
Section: Discussionmentioning
confidence: 58%
“…A patient information leaflet (PIL) is intended to provide patients with written information about the medication. Its main purpose is to provide patients with the necessary information about their medication in terms of its administration, precautions, and potential side effects . In our study, gender was highly associated with reading OTC product leaflets including side effects, contraindications, and proper storage conditions ( P < .05).…”
Section: Discussionmentioning
confidence: 70%
“…The so‐called pharmacist‐led medication appears as an important “chain link” to be encouraged and developed when considering the high level on confidence of people in pharmacists. For instance, in Sweden, where 42 products have been switched to OTC status since 2003, and where drugs like paracetamol have been available through nonpharmacy outlets since 2009 (Gedeborg et al, ), a consumer survey including 8,000 adults showed that pharmacy remains the most preferred OTC drug retailer (Westerlund et al, ). As key pivotal stakeholders in the decision‐making process (Bell et al, ; Chang et al, ; Gilmartin‐Thomas et al, ; Jonas, ), pharmacists are supposed to guide the consumer in making an appropriate choice and to identify inaccurate self‐diagnosis requiring a medical advice, so playing an important role as a point of access for providing OTC drug advice or physician referral when needed (Bell et al, ; Chang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The so-called pharmacist-led medication appears as an important "chain link" to be encouraged and developed when considering the high level on confidence of people in pharmacists. For instance, in Sweden, where 42 products have been switched to OTC status since 2003, and where drugs like paracetamol have been available through nonpharmacy outlets since 2009 (Gedeborg et al, 2017), a consumer survey including 8,000 adults showed that pharmacy remains the most preferred OTC drug retailer (Westerlund et al, 2017).…”
Section: Pharmacists Interventions In Analgesic Otc: Rationale Objmentioning
confidence: 99%
See 1 more Smart Citation